Designing a Self-Propelled Floating Cafe as a Sunset Tourist Attraction on the Kenjeran Coast of Surabaya - Izzul Fikry; M. Rizal Fahmi; Hayy Nur Abdillah; Nanda Dwi Wuryaningrum; Riko Satrya Fajar Jaelani Putra (Universitas Negeri Jakarta, 2026)
The Suramadu View Point in North Kenjeran, Surabaya, has considerable coastal tourism potential; however, existing facilities remain limited. This study proposes a self-propelled floating café as an alternative to enhance tourism activities. The methodology includes site surveys, hull design, resistance analysis, power prediction, general arrangement, and stability analysis. Considering shallow water constraints and operational simplicity, a monohull configuration was selected due to its ease of construction. The vessel has principal dimensions of 21.50 m length overall, 6.00 m breadth, 3.50 m depth, and 2.00 m draft, operating at 6 knots. The calculated total resistance is 43.70 kN, corresponding to a required propulsion power of 242 kW. A 277 kW engine is selected to ensure sufficient safety margin. The vessel is designed to support 48 hours of operation for 55 occupants with adequate tank capacities. Stability analysis under four loading conditions confirms compliance with IMO A.749 criteria. The results indicate that the proposed design is technically feasible, safe, and suitable for shallow coastal applications, offering a practical solution to support maritime tourism development.